2016
DOI: 10.1007/s00784-016-1770-y
|View full text |Cite
|
Sign up to set email alerts
|

Roughness and wettability effect on histological and mechanical response of self-drilling orthodontic mini-implants

Abstract: This treatment represents a step forward in the direction of reducing the time prior to mini-implant loading by increasing their stability during orthodontic treatment, without inducing bone fracture and tissue destruction during unscrewing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…In order to assess the effect of the surface treatments, follow-up times ranged from 12 h 20 to 10 [ 28 ] and 12 weeks [ 29 ]. The in vitro studies were published between 2010 [ 30 ] and 2023 [ 31 , 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to assess the effect of the surface treatments, follow-up times ranged from 12 h 20 to 10 [ 28 ] and 12 weeks [ 29 ]. The in vitro studies were published between 2010 [ 30 ] and 2023 [ 31 , 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Acid-etching of surfaces, as shown in clinical studies included in our review, has been investigated through immersion in various acids in solution, such as nitric [ 102 ], sulfuric [ 20 , 93 ], phosphoric [ 39 ], hydrofluoric [ 28 ] and hydrochloric acid [ 38 , 50 , 93 , 102 ]. No studies were included that compared the effectiveness of the various types of acid.…”
Section: Discussionmentioning
confidence: 99%
“…Several research studies have been performed concerning the surface characteristics of TADs, but there are less examining the contamination of TAD surfaces when being manipulated. Additionally, clear information about the finishing of the screw surface is lacking [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, other surface characteristics such as topography, in concert with surface wettability, may induce a synergistic effect on biological responses. It is reported that surface treatments with increased roughness and hydrophobicity lead to an increased BIC value and higher removal torques during unscrewing, causing bone fractures compared with as-machined mini-implants [ 34 ]. Further, we show here that surface roughness and wettability influenced the improvement of bone formation of each DNA-multilayer coating.…”
Section: Discussionmentioning
confidence: 99%